(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Pedagogical qualimetry emerged in the mid-20th century for the objective assessment of educational quality and effectiveness. It evolved from quantitative measures (like tests) to encompass qualitative aspects. Shaped by contributions from scholars like Galton, Binet, and Bloom, and influenced by the student-centered paradigm. In the context of modern challenges such as globalization and digitalization, it holds significant importance for managing educational processes, adapting standards, and identifying problems (particularly in the context of Uzbekistan). Qualimetry relies on theoretical foundations like quality concepts, measurement theory, monitoring, and a systemic approach, as well as pedagogical foundations like goal alignment and innovation. It plays a crucial role in ensuring educational quality, informing policy, and directing future personalized education.